Energy Consumption at Home: Insights for Sustainable Smart Home Marketing - Kose, Sirin Gizem; Cizer, Ece Ozer; Kazancoglu, Ipek (SPRINGER INTERNATIONAL PUBLISHING AG, 2023)
Energy consumption has been a vital subject for both energy producers and consumers. The intersection of energy consumption and home words are of increasing importance in both literature and practice. Households try to utilize energy in the most efficient and sustainable way. On the other hand, smart home technologies which let the households control their houses are on the rise. Those technologies also help balance the energy consumption and live in a more sustainable way. This study aims to underline the importance of smart home technologies to increase energy efficiency and pave the way for a more sustainable energy management. In line with this purpose, a bibliometric study has been conducted to enlighten the literature development in energy consumption and home subjects. The results are expected to be helpful for both literature and practice as well as energy providers and consumers.
Keywords: Energy consumption; Sustainable energy management; Smart home; FUNCTIONALITY; FEEDBACK; Science & Technology - Other Topics; Engineering; Operations Research & Management Science